2012
DOI: 10.1021/ic301189m
|View full text |Cite
|
Sign up to set email alerts
|

Tunability of Band Gaps in Metal–Organic Frameworks

Abstract: The tunability of the band gaps in Zn-based metal-organic frameworks (MOFs) has been experimentally demonstrated via two different approaches: changing the cluster size of the secondary building unit (SBU) or alternating the conjugation of the organic linker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
112
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 68 publications
6
112
1
1
Order By: Relevance
“…MOFs are excellent materials for a variety of applications such as gas storage 2 , drug-delivery 3 , and catalysis 4 . The interest in these materials is based on their high porosity and surface area, as well as the possibility of tuning its optical and electronic properties by changing the inorganic and/or the organic moieties 5 . Particularly, the photocatalytic behaviour characteristics of metal-organic frameworks have recently received considerable attention, from both fundamental aspects and practical applications 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are excellent materials for a variety of applications such as gas storage 2 , drug-delivery 3 , and catalysis 4 . The interest in these materials is based on their high porosity and surface area, as well as the possibility of tuning its optical and electronic properties by changing the inorganic and/or the organic moieties 5 . Particularly, the photocatalytic behaviour characteristics of metal-organic frameworks have recently received considerable attention, from both fundamental aspects and practical applications 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Note that this is the opposite of what is found in the work of Lin et al when they investigated the effect of cluster size on the band gap energy of ZnO clusters in a MOF. 25 In the case of the ZnO clusters, the top of the valence band and the bottom of the conduction band are located on the ZnO cluster, and it behaves much like a quantum dot. Here, the conduction band is locked in place, the band gap energy is determined by the energy of the orbital localized on the lone pair of the carboxylate and the Zn site.…”
mentioning
confidence: 99%
“…[78] By contrast, varying virtually the zinc-to-cobalt ion substitution ratio in the same Zn-based IRMOF-1 structure, band gaps ranging from semiconducting to metallic states could be achieved. [79] Alternatively, by comparing the computed HOMO -LUMOs of three existing MOFs that contain the same bdc ligands (namely, IRMOF-9, Zn5-BPDC, and CPO-7), Lin et al [80] concluded that increasing the size of the Zn-based metal cluster leads to a systematic red shift in optical band gaps. It has been predicted through a computational study that the band gap of the parent MOF-5 (, 3.5 eV) could be modified to absorb visible light by substituting the oxygen anion of the metal oxide core ZnO 4 , with sulfur anions (Zn 4 S: 3.30 eV) or selenium anions (Zn 4 Se: 2.91 eV) that allow a shift of the Fermi level due to their electron-rich properties.…”
Section: Electronic Structures Of Mofsmentioning
confidence: 99%